2005
DOI: 10.4315/0362-028x-68.5.986
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Electrolyzed Water in Inactivating Salmonella Enteritidis and Listeria monocytogenes on Shell Eggs

Abstract: The efficacy of acidic electrolyzed (EO) water produced at three levels of total available chlorine (16, 41, and 77 mg/ liter) and chlorinated water with 45 and 200 mg/liter of residual chlorine was investigated for inactivating Salmonella Enteritidis and Listeria monocytogenes on shell eggs. An increasing reduction in Listeria population was observed with increasing chlorine concentration from 16 to 77 mg/liter and treatment time from 1 to 5 min, resulting in a maximal reduction of 3.70 log CFU per shell egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…AEW has been reported to have strong bactericidal activity against many foodborne pathogens, including Escherichia coli O157:H7, Salmonella enteritidis, Salmonella typhimurium, Listeria monocytogenes (Venkitanarayanan et al, 1999;Kim et al, 2000;Fabrizio and Cutter, 2003;Park et al, 2004;Liao et al, 2007). Several studies have shown that AEW can be effective in reducing pathogenic bacteria on the surface of fruits and vegetables (Koseki et al, 2004a, b, c), eggs (Russell, 2003;Park et al, 2005), poultry carcasses (Kim et al, 2005), pork (Fabrizio and Cutter, 2005), seafood (Ozer and Demirci, 2006), and food processing facilities (Ayebah and Hung, 2005;Huang et al, 2008). However, the utilization of AEW has limited potential for long-term applications because of its strong acidity (pH < 2.7) (Guentzel et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…AEW has been reported to have strong bactericidal activity against many foodborne pathogens, including Escherichia coli O157:H7, Salmonella enteritidis, Salmonella typhimurium, Listeria monocytogenes (Venkitanarayanan et al, 1999;Kim et al, 2000;Fabrizio and Cutter, 2003;Park et al, 2004;Liao et al, 2007). Several studies have shown that AEW can be effective in reducing pathogenic bacteria on the surface of fruits and vegetables (Koseki et al, 2004a, b, c), eggs (Russell, 2003;Park et al, 2005), poultry carcasses (Kim et al, 2005), pork (Fabrizio and Cutter, 2005), seafood (Ozer and Demirci, 2006), and food processing facilities (Ayebah and Hung, 2005;Huang et al, 2008). However, the utilization of AEW has limited potential for long-term applications because of its strong acidity (pH < 2.7) (Guentzel et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Sato et al (2000) reported that the most effective use of electrolyzed water was washing with alkaline water to remove protein and other organisms followed by sanitizing with acidic water. Park et al (2005) also demonstrated that a combination of AlEW and AEW wash is equivalent to 200 mg/L of chlorinated water wash for reducing populations of S.enteritidis and L.monocytogenes on shell eggs. Fasenko et al (2009) found that the ability of AEW to reduce eggshell microbial load without negatively affecting hatchability or chick quality might make it a useful product for hatching egg sanitation.…”
mentioning
confidence: 99%
“…Actually, there were not many literatures with regard to AIEW, and very few effective applications of AIEW have been examined with respect to the use of electrolyzed water as a sanitizing agent (Koseki et al 2004). Koseki et al (2004) demonstrated that the maximum reduction of AIEW on lettuce was 1.8 log CFU/g, while Park et al (2005) found the efficacy of AIEW for L. monocytogenes was only 1.10 log CFU/g on shell eggs. Nevertheless, in this study, about 1 log CFU/g reduction was obtained at 15, 20, 25, 30, and 35°C.…”
Section: Resultsmentioning
confidence: 95%